Interview with Araceli Carrillo Pérez - Francisco Cuadrado Muñoz (ADIDE Federación, 2008)
Francisco Cuadrado, on behalf of AVANCES en Supervisión Educativa, interviews Araceli Carrillo Pérez, a member of the Andalucian autonomous Parliament belonging to the Socialist Party and was once a lecturer in favour of the Education Law for Andalucía, which lately became the first Education Act passed by a Spanish autonomous parliament after the Organic Act f Education (LOE) came in force. The Education Act of Andalucía was published on December 26th 2007, and came in force thirty days later.